THE COMPARISON OF HEROINE’S JOURNEY IN BRAVE MOVIE (2012) AND MOANA MOVIE (2016) - Gita Mutiara Ramadhanty (Universitas Islam Negeri Sunan Gunung Djati, 2020)
AbstractThe aim of this research is to discuss the comparison of the heroine’s journey in Brave movie (2012) and Moana movie (2016). To analyze both of them, the researcher uses the theory of hero’s journey by Christopher Vogler. Hero’s or heroine’s journey is a stage about growth and passage each stage of journey must be passed successfully then could be called as a hero or heroine. Not only analyze the hero’s journey, but also compare it by using comparative literature theory. This research is designed as a literary criticism. The method used in this research is comparative literature method. The results of the research indicate that the heroine in Brave and Moana movie, both of the heroine have gone through several stages in Heroine's Journey. There is one difference in the two movies when viewed from the heroine's journey. From twelve hero’s journey by Vogler, the heroine in Brave movie goes through 9 stages of hero’s journey. Meanwhile the heroine in Moana movie passed 10 stages of the hero’s journey.Keywords: Comparative Literature, Movie, Hero’s Journey.